Significance of Extra-Esophageal Symptoms in Pediatric Gastroesophageal Reflux Disease - Košec, Andro; Žaja, Orjena; Matovinović, Filip; Jelavić, Boris; Baudoin, Tomislav (International Archives of Otorhinolaryngology, 2020)
Introduction Current practice guidelines in gastroesophageal reflux disease (GERD) often require invasive diagnostic testing.Objective The aim of the present study was to evaluate the significance of extra-esophageal symptoms and reliability of a screening risk score that is simple to use.Methods A longitudinal retrospective single-institution cohort study. Setting: A university clinical hospital tertiary referral center. The present study enrolled pediatric patients with symptoms suggestive of GERD: epigastric pain, occasional nausea, regurgitation, tasting acid in the oral cavity, chronic cough, hoarseness of voice, frequent throat clearing. The patients underwent 24-hour esophageal pH monitoring and fiber-optic laryngoscopy. The correlations between the local findings, anamnestic and objective measurement data were analyzed.Results The present study evaluated 89 pediatric patients. Patients with asthma presented significantly more often with adjoining gastrointestinal symptoms (p = 0.0472). Patients that were obese were linked to a higher rate of reports of gastrointestinal symptoms (p = 0.0495). After the patients had been assigned to newly developed risk groups, obesity showed to be significantly more frequent in patients placed in higher risk groups (p < 0.0001) for a positive GERD diagnosis.Conclusion Patients with leading symptoms of asthma presented significantly more often with adjoining gastrointestinal symptoms. Obesity showed to be significantly more frequent in patients placed in higher risk groups for a positive GERD diagnosis.
Keywords: diagnostics; obesity; pediatric gastroesophageal reflux disease; screening